An overview: analysis of ultrasonic-assisted extraction’s parameters and its process - Zaini, Ahmad Syahir; Sulaiman, Sarina; Mel, Maizirwan; Othman, Maizatulnisa; Sulaiman, Siti Zubaidah (IOP Publishing, 2020)
Previously, there were many extraction methods that had been done on extracting the oil such as centrifugation, chilling and thawing, hot and cold extraction, on seeds, waste products and plants. Based on those oil extraction methods (OEM), further study is needed to develop more effective processes as most of the methods were having many disadvantages in term of time, cost, quality and safety. Ultrasonic-assisted extraction (UAE) is used in this project as it is a rapid and effective extraction technique that uses ultrasound to generate rapid movement of solvents, resulting in a higher mass transfer speed as well as acceleration of extraction. Compared to other advanced extraction techniques, UAE is more economic, eco-friendly, and convenient by the reduction of time consumption, higher oil quality and cost reduction. The principle of acoustic cavitation ultrasound which is explained by a series of compression and rarefaction waves induced in the molecules of the medium and the collapse of the bubble during the process of UAE may be discussed. Parameters involved also play the important role in the extraction such as extraction time (ET), extraction temperature (ETem), solvent to material ratio (S/M Ratio) and type of solvent selected. Thus, the paper discusses the application of UAE on oil extraction.